Intracranial Gliofibroma: A Case Report and Review of the Literature - Patricia Gargano; Graciela Zuccaro; Fabiana Lubieniecki (Case Reports in Pathology)
Gliofibroma is a rare tumor with biphasic morphology, commonly occurring in the first two decades of life. Currently, the tumor is not listed as a distinct entity in the current World Health Organization (WHO) classification of central nervous system tumors. As its biological behavior, histogenesis, and prognostic factors are still debated, the aim of this paper was to describe a case of a gliofibroma and to update the data about these lesions. Hence, we present here clinical symptoms, pathological findings, and evolution observed in a child with gliofibroma. A 10-year-old girl with seizures was referred for study. Neuroimaging showed a hemispheric hyperdense tumor with little peritumoral edema and no mass effect. The tumor was totally removed. Histologically, the tumor consisted of a mixture of glial cells and collagen-rich stroma. Immunohistochemical examination revealed positive staining for GFAP, CD 99, S100, and vimentin. EMA staining showed a paranuclear dot pattern in only few cells in isolated areas. These findings of a glial component with collagenous stroma were consistent with a desmoplastic glioma. Because of the rarity of this entity, we believe it is important to report every case in order to adequately analyze and categorize the tumor in the next WHO classification.